PEMANFAATAN PEKARANGAN RUMAH UNTUK MENINGKATKAN KETAHAN PANGAN PADA MASA PANDEMI COVID-19 - Tineu Indrianeu; Iman Hilman; Elgar Balasa Singkawijaya; Erni Mulyanie (LP2M STP Mataram, 2021)
Food security can indicate the availability of fulfillment in the form of access to food resources so that it can meet current basic needs. The service is carried out by optimizing the results of previous dedication, namely related to community participation in domestic waste management with a waste bank model, the use of house yards to improve food security is in Sindanggalih Village RW 03, Gununggede Village, Kawalu District, Tasikmalaya City, which is still lacking. The method used in this service is utilizing the land, among others, sketching the yard, making a stake as a measure and marking the yard that will be used for planting activities, conducting training in the form of yard land management activities and plant cultivation techniques, and monitoring and evaluation carried out to know the progress of the implementation of activities. Partners in this service activity partnered with a group of women managing waste banks, namely